Tarifliche Öffnung in Deutschland: Ausmaß, Determinanten, Auswirkungen - Tobias Brändle; Wolf Dieter Heinbach; Michael F. Maier (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– Given the recent financial crisis, the German labour market performs relatively well. This has not been the case until recent years: collective bargaining and the rigid system of wage setting have been often cited as one of the reasons for Germany's high structural unemployment. Contrary, a reform process has started at least since the mid-1990s, introducing measures of flexibility and decentralization to the formally rigid system of wage setting. This article summarises the developments of possible and actual flexibilisation of collective bargaining contracts via so called hardship or opening clauses. A literature review sums up the scientific progress that had been made at the beginning of the research project and shows which gaps were to fill. Lacking data, the first parts of the project investigate on the actual existence and shape of opening clauses and create a new data set to measure the incidence of opening clauses in collective bargaining agreements in West German manufacturing sector for the years 1995 to 2007, the IAW data set on opening clauses. Using this, we analyse the determinants of the introduction of opening clauses on the industry level and of their actual implementation on the firm level. The latter parts of the project focus on the relation between opening clauses and measures of firm performance, especially considering wages and job growth. The results show that opening clauses are more and more common and that a more diversified wage structure and higher job growth is observed.
Keywords: J51; J63; C21; 330; Tarifvertrag; Tarifrecht; Öffnungsklausel; Tarifpolitik; Flächentarifvertrag; Firmentarifvertrag; Tarifpartner; Lohnsenkung; Arbeitszeitflexibilität; Arbeitskosten; wirtschaftliche Situation; Export; internationaler Wettbewerb; Lohnstruktur; Beschäftigtenzahl; Betrieb; Beschäftigungspolitik; Einkommenspolitik; Lohnpolitik